Features of self-control indicators in wellness walking elder people - Myhalchuk T.D (Kharkov National Pedagogical University, 2012)
The article examines the specifics of organization of control and self-control in health walking with elderly people. Particular attention is paid to the use of self-control indicators in the health training. Disclosed the direction of the choice of dose of physical activity. Allocated basis of motivation of older people to recreational pursuits walking. Mode walking with varying heart rate and the rate has been divided into three zones. Described the influence of recreational walking on the system, provide recommendations leading experts in the field. There is determined a role and place of pedagogical control and self-control as an integral part of fitness training, which enables to control physical activity.